Um Esquema de Comunicação MIMO Multiusuário com Modulação Espacial - Pizzio, Robinson; Uchôa-Filho, Bartolomeu F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2016)
In this paper we propose a multiple-input, multiple-output (MIMO) multiuser communication scheme with spatial modulation. The motivation is to improve the system’s spectral efficiency, by sending information through the index which indicates a subset of active antennas. An improved method based on phase shifts at the base station increases the spatial detectability. Computer simulation shows the improved biterror rate over a reference scheme under the same spectral efficiency.